PENGARUH IMPRESSION MANAGEMENT DAN KOMPETENSI PROFESIONAL GURU SENI BUDAYA TERHADAP SIKAP BELAJAR SISWA SMAN DI KAB TANGERANG - Qodriyah, Laelatul; Prihantoro, Edy (FIKRAH, 2024)
This study aims to determine the influence of impression management and professional competence of Arts and Culture teachers on students' learning attitudes. The population in this study is students of SMAN 1 Tangerang and SMAN 30 Tangerang in 2024, with a research sample of 87 students taken using the solvin formula. The data collection technique was through a questionnaire, with instruments as many as 41 statement items. Meanwhile, the data analysis is quantitative with descriptive statistical techniques, simple regression correlation analysis, and multiple regression correlation analysis. The results of the study were: there was a significant influence of impression management on students' learning attitudes by 51.5%, there was a significant influence of professional competence of cultural arts teachers on students' learning attitudes by 55.9%, and there was a significant influence of impression management and professional competence of cultural arts teachers simultaneously on students' learning attitudes by 62.8%. These results show that impression management and professional competence of cultural arts teachers have a considerable impact on the positive change of students' learning attitudes.